The use of Quranic and Prophetic Teaching Methods (QPTMs) in teaching non-religious subjects in Islamic international schools in Malaysia - Eissa, Manar; Khalid, Madihah (2017)
The Islamic tradition is rich in teaching methods used historically. A number of studies have been conducted on the use of the teaching methods derived from Quran and Sunnah in teaching Islamic studies. However, the integration of Quranic and Prophetic teaching methods (QPTMs) in teaching non-religious subjects is not yet explored. Hence, this research study attempts to assess the use of selected teaching methods derived from Quran and Sunnah in teaching non-religious subjects, based on their effectiveness in teaching and their ability to engage students in learning. The quantitative data were collected from 87 secondary school teachers who teach non-religious subjects in several Islamic International Schools in Selangor, Malaysia, using a survey questionnaire developed by the researchers. The quantitative data were analyzed using descriptive statistics and chisquare technique to find out if there are any difference between the four subjects of Mathematics, Science, Language and Humanities in terms of using the different QPTM methods identified. The findings of the study revealed that from the teachers’ perspectives, the selected QPTMs are effective methods of teaching and able to engage students in learning. However, the chi-square test shows no significant difference between the subjects in terms of using the different QPTMs. The findings from the study may steer school leaders to increase the knowledge of teachers on QPTMs, and the prospect of using these methods in teaching non-religious subjects. Additionally, the information obtained can draw the attention of curriculum developers to include the QPTMs in teaching non-religious subjects to enhance the implementation of integrated curriculum.